Redesigning a product (Video Education Australasia, 2010)
"This program demonstrates the various methods, techniques and strategies designers use when redesigning a product. It describes the principles of intellectual property and the importance of acknowledging the intellectual property of others. Viewers will develop an understanding of the role of the designer when a product is redesigned, and learn to develop a structured approach towards the design process."--in container.